Open fractures of the tibia in HIV positive patients: a prospective controlled single-blind study. - Harrison, W; Lewis, C; Lavy, C (2004)
Twenty-seven patients with severe open fractures were studied prospectively analysing infection and union as outcome measures. A standard treatment regime was applied. Seven patients were HIV positive, and 20 patients HIV negative. Wound infection and delayed union were more common in HIV positive patients. The difference in rate of infection was statistically significant (P = 0.020), while that in union did not quite reach significance (P = 0.059). The authors have developed an algorithm for treatment of these injuries in areas of high seroprevalence of HIV infection.